Physicochemical Properties of Malaysian Commercial Chicken Sausages - Huda, Nurul; Wei, Lim Hoo; Jean, Alistair T.L.; Ismail, Ishamri (International Journal of Poultry Science, 2010)
Sausage is becoming more popular to the Malaysian consumers. A study on quality characteristics for chicken sausages marketed in Malaysia was conducted to gauge the trend of marketed sausages today. A total of ten samples of chicken sausages from different brands were analyzed to determine the proximate composition, calcium and sodium contents, colour, folding test and textural properties (hardness, springiness, cohesiveness, gumminess, chewiness and shear force). The moisture, protein, fat and ash contents for chicken sausages were significantly different, in the range of 56.48-68.85%, 7.03-14.14%, 4.91-18.48% and 2.17-3.30%, respectively. The range of carbohydrate content was 6.69-21.59%. The calcium and sodium contents were varied in chicken sausages. The lightness value (L*) of sausage was significantly different among the samples in the range of 44.42-65.54. All chicken sausages samples tested in this study show good gel strength with their folding test at more than 4.0. The hardness, springiness, cohesiveness, gumminess, chewiness and shear force ranged between 3.84-7.25 kg, 12.79-15.65 mm, 0.25-0.41 ratio, 1.28-2.58 kg, 16.81-33.01 kg.mm and 0.58-1.95 kg, respectively. The results of this analysis showed that sausages produced by different manufacturers will varied significantly in quality and physicochemical properties.